Evaluating the role of coastal hypoxia on the transient expansion of microencruster intervals during the early Aptian - Hüter, Alexander (Dr. rer. nat.); Huck, Stefan (Dr. rer. nat.); Heimhofer, Ulrich (Prof. Dr. rer. nat.); Bodin, Stéphane (Prof. Dr. rer. nat.); Weyer, Stefan (Prof. Dr. rer. nat.); Jochum, Klaus P. (Dr. rer. nat.); Roebbert, Yvonne (Dr. rer. nat.); Immenhauser, Adrian (Prof. Dr.) (2020)
Worldwide, a growing number of modern coastal marine ecosystems are increasingly exposed to suboxic- or even anoxic conditions. Low seawater oxygen levels trigger significant ecosystem changes and may result in mass mortality of oxygen-sensitive biota. The applicability of observations from recent (anthropogenically influenced) suboxic coastal settings to fossil anoxic shallow-marine environments is, however, as yet poorly explored. The test case documented here are upper Barremian to lower Aptian strata in the Lusitanian Basin (Ericeira section, Portugal). These are characterized by the transient demise of rudist–coral communities and the rapid establishment of microencruster facies in the vacant ecological niches. The hypothesis is tested that the temporal expansion of the microencrusting organism \(Lithocodium aggregatum\) took place in response to platform-top seawater oxygen depletion. We critically discuss the outcome of a multi-proxy palaeoseawater redox approach (e.g. Rare Earth Elements (REEs), U isotopes and palaeoecology) and put the robustness of the proxies applied here to the test. This is done by considering issues with these methods in general but also emphasizing the significance of terrigenous contamination and fractionation effects. Data shown here document that evidence for coastal seawater oxygen depletion in the prelude of Oceanic Anoxic Event (OAE) 1a is lacking, and hence, anoxia was not the driving mechanism for the demise of rudist–coral ecosystems in the proto-North Atlantic platform setting studied here. In contrast, well-oxygenated early Aptian platform-top water masses are proposed for this site. Geologically short (decades to millennia) fluctuations in seawater oxygen levels cannot be excluded, however. But even if these took place, they offer no explanation for the Kyr to Myr-scale patterns discussed here. The present paper is relevant as it sheds light on the complexity of mechanisms that drive punctuated Early Cretaceous coral–rudist ecosystem turnover, and assess ...